Microstructure analysis of NiO nanocrystals and enhanced photocatalytic activities of NiO-CdS nanocomposites - Sharma, Saurabh K.; Kalita, Manos P. C. (Journal of materials science. Materials in electronics, 2022)
A comprehensive study on the microstructure of chemically prepared NiO nanocrystals has been carried out using various forms of Williamson–Hall (WH) formulation of X-ray diffraction (XRD) line profile analysis viz. uniform deformation model (UDM), uniform stress deformation model (USDM), uniform deformation energy density model (UDEDM) and modified WH (MWH) method. The optical properties and simulated sunlight-induced photocatalytic activities for methylene blue (MB) dye degradation of these nanocrystals have been studied. The crystallite size obtained from the WH analyses is approximately 12 nm. The dislocation density of the nanocrystals is found to be 1.7 × 10 16 m −2 , which gives rise to lattice strain of 3.0 × 10 –3 . The stress and energy density of the nanocrystals are found to be 765 MPa and 1199 kJ m −3 , respectively. The band gap of the nanocrystals is 4.23 eV, and they show emissions related to nickel vacancy and nickel interstitial defects. The nanocrystals have been found to degrade 26% dye after 120 min of light irradiation. Moreover, the NiO nanocrystals have been used to produce nanocomposites by synthesizing CdS nanocrystals over it. The NiO-CdS nanocomposites have been found to exhibit significantly enhanced photocatalytic activities as compared to the NiO nanocrystals. Formation of heterojunctions between NiO and CdS has been attributed to the observed enhancement in the photocatalytic activities of the nanocomposites.